Keterampilan Mendengarkan Secara Aktif dalam Komunikasi Interpersonal - Martoredjo, Nikodemus Thomas (Bina Nusantara University, 2014)
Interpersonal communication is transactional and two-way direction. Therefore active listening skills play a key role in interpersonal communication. These active listening skills can have a positive impact on communication and at the same time creating a better relationship. So it is very useful to improve the skills of active listening. This paper intends to reveal the important role of active listening skills in interpersonal communication, identifying the challenges that exist within it both internally and externally as well as indicate the action that needs to be developed to improve these skills.